The Iron Assimilatory Protein, FEA1, from Chlamydomonas reinhardtii Facilitates Iron-Specific Metal Uptake in Yeast and Plants - Narayanan, Narayanan N.; Ihemere, Uzoma; Chiu, Wai Ting; Siritunga, Dimuth; Rajamani, Sathish; Singh, Sareena; Oda, Saharu; Sayre, Richard T. (Frontiers in Plant Science, 2011)
We demonstrate that the unique green algal iron assimilatory protein, FEA1, is able to complement the Arabidopsis iron-transporter mutant, irt1, as well as enhance iron accumulation in FEA1 expressing wild-type plants. Expression of the FEA1 protein reduced iron deficient growth phenotypes when plants were grown under iron limiting conditions and enhanced iron accumulation up to 5-fold relative to wild-type plants when grown in iron sufficient media. Using yeast iron uptake mutants, we demonstrate that the FEA1 protein specifically facilitates the uptake of the ferrous form of iron. Significantly, the FEA1 protein does not increase sensitivity to toxic concentrations of competing, non-ferrous metals nor facilitate their (cadmium) accumulation. These results indicate that the FEA1 protein is iron specific consistent with the observation the FEA1 protein is overexpressed in cadmium stressed algae presumably to facilitate iron uptake. We propose that the FEA1 iron assimilatory protein has ideal characteristics for the iron biofortification of crops and/or for facilitated iron uptake in plants when they are grown in low iron, high pH soils, or soils that may be contaminated with heavy metals.